Pengaruh Proses Rekrutmen Terhadap Kinerja Pegawai Bagian Produksi Perumda Tirta Mayang Kota Jambi - Julio Wandar Pratama (Science of Management and Students Research Journal (SMS), 2022)
The purpose of this study was to determine and analyze the influence of recruitment process on the performance of production employee at PERUMDA tirta Mayang Kota Jambi. This type of research is quantitative methods. The sample in this study were production employee of PERUMDA Tirta Mayang Kota Jambi, amounting to 94 respondents. The data used is primary data. The data was collected using a questionnaire. The analytical method used is descriptive analysis method and the method of statistical analysis by simple linear regression analysis (Y = 18,081 + 0,307 X), in which the processing of data using SPSS 22 for windows and the method of hypothesys analysis by t-test. The results of this study indicate that : recruitment process variable has a significant effect on performance of production employee. Based on the result of R Square of 0,191 which show contribution of independent variable, namely employee performance by 19,1% while the remaining 81,9% explained by other variables that are not in the research regression model. The conclusion of the partial test is that recruitment process has a significant effect on performance of production employee at PERUMDA Tirta Mayang Kota Jambi, this is evidenced by the value of tcount > ttable (4,959>1,662).